Lack of an association between spleen volume and risk of pneumococcal infection in cancer patients: a nested case-control study - Ibuki Kurihara; Hajime Yamazaki; Sakura Kato; Noriko Oyama-Manabe; Hitoshi Sugawara (BMC Infectious Diseases)
Abstract Background The spleen is a key organ in preventing pneumococcal infection, especially in patients with immunocompromised condition such as those with cancer. Previous studies have shown that a small spleen volume in pneumococcal pneumonia patients is associated with severe disease course. However, it is unknown whether a small spleen increases risk of pneumococcal infection. We investigated the association between spleen volume and risk of pneumococcal infection. Methods This study was a retrospective cohort study using a nested case-control design and involved adult patients with malignancy who underwent chest and/or abdominal CT scans from January 1, 2008, to September 30, 2020, at a tertiary care center in Japan. Exclusion criteria comprised patients diagnosed with hepatic cirrhosis, leukemia, lymphoma, and/or post-splenectomy. From the cohort group that met all selection criteria (n = 22475), we identified all incident cases of pneumococcal infection (pneumococcal pneumonia and/or invasive pneumococcal diseases) and matched them with four controls by age, sex, and follow-up duration. Odds ratios (ORs) for the association between spleen volume and pneumococcal infection were estimated using conditional logistic regression models adjusted for body surface area, performance status, Charlson comorbidity index, and metastatic cancer. Results The median spleen volume was 85.8 (interquartile range, 65.8–120.8) cm3. Over a median follow-up of 4.95 (interquartile range, 1.54–9.25) years, 60 patients were diagnosed with pneumococcal infection (20 with invasive pneumococcal disease and 40 with pneumonia without invasive pneumococcal disease) and matched with 240 controls. Spleen volume reduction (per 10 cm3) did not increase risk of pneumococcal infection in a crude analysis [OR 1.04 (95% CI 0.98–1.11)]. The outcome remained unchanged in the multivariable analysis (OR 1.01 [95% CI 0.95–1.08]). Conclusions Small spleen volume did not increase risk of pneumococcal infection in cancer patients.